2022
DOI: 10.1089/g4h.2021.0228
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility, Acceptability, and Preliminary Impact of Full-Body Interaction on Computerized Cognitive Training Based on Instrumental Activities of Daily Living: A Pilot Randomized Controlled Trial with Chronic Psychiatric Inpatients

Abstract: Objective: To conduct a pilot randomized control trial to assess the feasibility and acceptability of full-body interaction cognitive training (FBI-CT) inspired by instrumental activities of daily living in chronic psychiatric inpatients and to explore its preliminary impact on cognitive and noncognitive outcomes. Materials and Methods: Twenty psychiatric inpatients met the inclusion criteria and were randomly allocated to the FBI-CT group (n = 10) or the tablet-based CT group (T-CT) (n = 10). Neuropsychologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…This program was administered to chronic psychiatric inpatients instead of stroke patients due to restrictions related to the COVID-19 pandemic in accessing the stroke population. The findings of this pilot randomized controlled trial revealed promising preliminary outcomes regarding the impact of the computerized CT program on participants' cognitive and noncognitive domains ( 54 ).…”
Section: Methodsmentioning
confidence: 99%
“…This program was administered to chronic psychiatric inpatients instead of stroke patients due to restrictions related to the COVID-19 pandemic in accessing the stroke population. The findings of this pilot randomized controlled trial revealed promising preliminary outcomes regarding the impact of the computerized CT program on participants' cognitive and noncognitive domains ( 54 ).…”
Section: Methodsmentioning
confidence: 99%